Wagering against TINA: Nothing to lose but our... / Apostando contra TINA: Nada que perder salvo nuestrxs… - JOFFRE-EICHHORN, Hjalmar Jorge (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT In a context dominated by TINA (“There Is No Alternative” to neoliberal capitalism and liberal democracy), the notion of the wager, as conceived by Pascal and Boaventura de Sousa Santos, constitutes a potentially crucial means of re-igniting our capacities for taking action toward social and cognitive justice. This article proposes to further develop the theory and practice of wagering by (1) critically engaging with some of Santos’ propositions; (2) putting him into dialogue with the work of Alain Badiou, in particular his notions of fidelity and courage; and (3) suggesting a decolonized reading of Kant’s and Foucault’s What is Enlightenment?. RESUMEN En un contexto global dominado por la lógica destructiva de TINA (“There Is No Alternative” al sistema capitalista y la democracia liberal), la noción de la apuesta, ideado por Pascal y Santos, tiene mucho potencial para reanimar nuestras luchas por la justicia social y cognitiva. Este artículo propone profundizar la teoría y práctica de la apuesta mediante (1) una investigación crítica de la propuesta de Santos; (2) un diálogo entre Santos y la obra de Alain Badiou, en particular sus nociones de fidelidad y coraje; y (3) una lectura descolonizada de ¿Qué es la ilustración?, de Kant y Foucault..